Who Should Rather Undergo Transesophageal Echocardiography to Determine Stroke Etiology: Young or Elderly Stroke Patients? - Strecker, Christoph; Günther, Felix; Harloff, Andreas (Frontiers in Neurology, 2020)
Introduction: The indication of transesophageal echocardiography (TEE) in acute stroke is unclear. Thus, we systematically studied the impact of TEE on determining stroke etiology and secondary prevention in patients of different age-groups with cryptogenic stroke. Methods: Four hundred and eighty five consecutive patients with acute retinal or cerebral ischemia were prospectively included and underwent routine stroke workup including TEE. Stroke etiology was identified according to the TOAST classification and patients were divided in those with determined and cryptogenic stroke etiology without TEE results. Then, the frequency of high- and potential-risk sources in TEE was evaluated in <55, 55–74, and ≥75 year-old patients with cryptogenic stroke etiology. Results: Without TEE, stroke etiology was cryptogenic in 329(67.8%) patients and TEE determined possible etiology in 158(48.4%) of them. In patients aged <55, 55–74, ≥75, TEE detected aortic arch plaques ≥4 mm thickness in 2(1.2%), 37(23.0%), and 33(40.2%) and plaques with superimposed thrombi in 0(0.0%), 5(3.1%), and 7(8.5%); left atrial appendage peak emptying flow velocity ≤30cm/s in 0(0.0%), 1(0.6%), and 2(2.4%), spontaneous echo contrast in 0(0.0%), 1(0.6%), and 6(7.3%), endocarditis in 0(0.0%), 0(0.0%), and 1(1.2%) and patent foramen ovale (PFO) plus atrial septum aneurysm (ASA) in 18(20.9%), 32(19.9%), and 14(17.1%), respectively. TEE changed secondary prevention in 16.4% of these patients following guidelines of 2010/11 and still 9.4% when applying the guidelines of 2020. Conclusions: TEE was highly valuable for determining stroke etiology and influenced individual secondary prevention based on available treatment guidelines and expert opinion in most cases. In young patients the impact of TEE was limited to the detection of septal anomalies. By contrast, in older patients TEE detected high numbers of complex aortic atheroma and potential indicators of paroxysmal atrial fibrillation.